Preparation method of ultrahigh-strength weathering steel based on phosphorus regulation and control

Through the ultra-high-strength weathering steel preparation method regulated by phosphorus, the problems of high content and insufficient strength of weathering steel alloys are solved, and hot-rolled thin plates with high strength, high toughness, corrosion resistance are prepared, reducing the alloy cost.

CN120443051APending Publication Date: 2025-08-08XINJIANG BAYI IRON & STEEL CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510722569.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-05-30
Publication Date
2025-08-08

AI Technical Summary

Technical Problem

The high content of existing weathering steel alloys leads to an increase in costs, and the strength levels are mostly limited to 345-460MPa levels, which cannot meet the high-strength needs.

Method used

The ultra-high-strength weathering steel preparation method is adopted for phosphorus regulation. By controlling the composition of molten iron and smelting processes, including top-bottom reblowing converter smelting, LF furnace refining, continuous casting and controlled rolling and cold-controlled processes, the Cu, Cr, P and other elements are reasonably added, combined with Ti microalloyation and controlled rolling and cold-controlled processes, stable titanium carbide is formed, grains are refined, and corrosion resistance is improved.

Benefits of technology

The preparation of ultra-high strength and high toughness hot-rolled thin sheets has been achieved, and the corrosion resistance and welding performance have been significantly improved, reducing alloy costs and meeting high strength requirements.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120443051A_ABST
    Figure CN120443051A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of ferrous metallurgy, and particularly discloses a preparation method of ultrahigh-strength weathering steel based on phosphorus regulation and control, and the weathering steel comprises the following components in percentage by mass: 0.04 to 0.06 w percent of C, 0.30 to 0.50 w percent of Si, 0.45 to 0.55 w percent of Mn, 0.22 to 0.30 w percent of Cu, 1.25 to 1.35 w percent of Cr, 0.075 to 0.085 w percent of P, less than or equal to 0.005 w percent of S, 0.025 to 0.040 w percent of Al, 0.085 to 0.10 w percent of Ti, 0.0015 to 0.0035 w percent of Ca, less than or equal to 0.0050 w percent of N and the balance of Fe and inevitable impurities. Through the synergistic effect of corrosion-resistant elements such as Cu, Cr and P, the surface stability of weathering-resistant steel is improved, a hot-rolled sheet with ultrahigh strength, high toughness and high corrosion resistance is obtained in cooperation with Ti microalloying and controlled rolling and controlled cooling processes, meanwhile, titanium is added to be combined with carbon in steel to form stable titanium carbide (TiC), and the titanium carbide (TiC) serves as a nucleation mass point to refine grains and reduce grain boundary corrosion of steel, so that the corrosion resistance of the steel is improved. And the corrosion resistance and the welding performance of the material are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of iron and steel metallurgy, and in particular to a method for preparing ultra-high strength weathering steel based on phosphorus regulation. Background Art

[0002] With the acceleration of global industrialization and the frequent occurrence of extreme climate events, the performance shortcomings of traditional steel in complex environments are becoming increasingly apparent. Ordinary carbon steel is susceptible to corrosion in humid, saline, or industrially polluted environments, resulting in reduced structural strength, shortened service life, increased maintenance costs, and even safety hazards.

[0003] The corrosion protection of traditional steel mainly relies on external painting or plating technology, but the coating is easy to age and fall off, and requires frequent maintenance. For example, the painting and maintenance costs of infrastructure such as bridges and offshore platforms account for more than 40% of the total life cycle costs. At the same time, as structures develop towards lightweight and large spans, higher requirements are placed on the strength of steel. Although ordinary low-alloy high-strength steel has improved its strength, its corrosion resistance has been limited. It still faces problems such as pitting corrosion and stress corrosion cracking in marine atmospheres or acidic environments. This contradiction has prompted researchers to start from the intrinsic properties of the material and explore the synergistic optimization of performance through alloy design and material microstructure regulation.

[0004] Current weathering steel forms a dense rust layer by adding elements such as Cu, P, and Cr, reducing the corrosion rate to 1 / 8 of that of ordinary steel. However, existing weathering steel has two major defects: one is the high alloy content, which leads to rising costs (such as high Ni content); the other is that the strength level is mostly limited to 345-460MPa. Summary of the Invention

[0005] The purpose of the present invention is to provide a preparation method of ultra-high strength weathering steel based on phosphorus regulation, so as to solve the problem that the existing weathering steel has a high alloy content, resulting in rising costs and the strength level is mostly limited to 345-460MPa.

[0006] To achieve the above objectives, the present invention provides a basic solution: a preparation method of ultra-high strength weathering steel based on phosphorus regulation, wherein the composition weight percentage of the weathering steel includes C: 0.04-0.06w%, Si: 0.30-0.50w%, Mn: 0.45-0.55w%, Cu: 0.22-0.30w%, Cr: 1.25-1.35w%, P: 0.075-0.085w%, S≤0.005w%, Al: 0.025-0.040w%, Ti: 0.085-0.10w%, Ca: 0.0015-0.0035w%, N≤0.0050w%, and the rest is Fe and unavoidable impurities, and further comprises the following steps:

[0007] S1. First, pre-treat the molten iron to make the S content in the molten iron ≤ 0.003w%;

[0008] S2. Add the pretreated molten iron into a top-bottom combined-blowing converter for oxygen blowing smelting, control the converter endpoint C content to 0.03-0.045w%, P content ≤ 0.010w%, S content of the molten steel ≤ 0.0070w%, N content ≤ 0.0020w%, and the converter tapping temperature to 1630-1660°C;

[0009] S3, after the converter smelting is completed, tapping is carried out. During the converter tapping process, pre-melted slag is first added to the ladle. The amount of pre-melted slag added is 300kg per furnace of steel. When the converter taps to 1 / 3 of the molten steel volume, low-carbon ferrochrome and low-carbon ferromanganese are added to the ladle. When the converter taps to 2 / 3 of the molten steel volume, ferroaluminum is added to the molten steel. The amount of ferroaluminum added is 1.0-1.2kg per ton of steel. The temperature of the molten steel in the ladle is controlled to be 1575-1590°C.

[0010] S4. Before refining, the molten steel is first fed with aluminum wire for deoxidation, and then the ladle is sent to the LF furnace for refining. The initial refining temperature of the LF furnace is not lower than 1570℃, and the power-on temperature-raising time is not more than 20 minutes. Active lime and bauxite are added to each batch of steel when the LF furnace is powered on. Foaming agent is added in three equal amounts 2 to 3 minutes after the power is turned on, with an interval of 5 minutes between each addition. 90 to 110 kg of aluminum particles are added 10 minutes after the power is turned on. After 10 minutes of white slag formation, argon is blown from the bottom for desulfurization for 5 minutes, and then ferrotitanium is added. After bottom blowing and stirring for 12 to 16 minutes, the molten steel is continuously cast and the cooling time is more than 4 to 6 minutes before pouring.

[0011] S5. During the continuous casting of slabs, a low-viscosity continuous casting mold slag is used. The viscosity of the mold slag at 1300°C is 0.12-0.14 Pa·s, the binary basicity CaO / SiO2 of the mold slag is 1.2-1.3, the CaF2 content in the mold slag is 4-5w%, the molten steel superheat is 25-32°C, the insertion depth of the submerged nozzle in the molten steel in the crystallizer is 150-160mm, the continuous casting casting speed is controlled at 1.2-1.3m / min, and the center segregation of the continuously cast slabs is not greater than level 1.0 according to the low-power detection of hot acid immersion of the continuously cast slabs;

[0012] S6. The slab after continuous casting is hot rolled, the furnace charging temperature is 450-620°C, the slab heating temperature is 1240-1260°C, the end temperature of rough rolling is 1140-1155°C, the start temperature of finishing rolling is 890-930°C, the end temperature of finishing rolling is 875-895°C, the steel plate after finishing rolling is laminar cooled, the cooling rate of laminar cooling is 15-18°C / s, and the coiling temperature is 565-580°C.

[0013] The beneficial effects of the present invention are: through the synergistic effect of corrosion-resistant elements such as Cu, Cr, and P, the surface stability of weathering steel is improved, and ultra-high strength, high toughness, and high corrosion resistance hot-rolled thin plates are obtained by combining Ti microalloying and controlled rolling and controlled cooling processes. At the same time, titanium is added to combine with carbon in steel to form stable titanium carbide (TiC), which acts as a nucleation particle to refine the grains, reduce intergranular corrosion of the steel, and improve the corrosion resistance and welding performance of the material.

[0014] Option 2 is the preferred option of the basic option. In S3, the main components of the pre-melted slag include: CaO content 35-40w%, Al2O3 content 36-40w%, CaF2 content ≤5w%, and Al content 15-18w%. After the converter is tapped, the pre-melted slag melts rapidly, and the slag density is lower than that of the molten steel, so it floats on the surface of the molten steel, isolating the molten steel from the air.

[0015] Option 3 is the preferred option of the basic option. In S4, the foaming agent is a mixture of limestone and dolomite with a mass ratio of 3:2, a particle size of 5 to 30 mm, and an addition amount of 70 to 80 kg per furnace of steel.

[0016] Option 4 is the preferred option of the basic option. In S4, after refining in the LF furnace, the molten steel is fed with 220-350m calcium wire to prevent nitrogen increase in the molten steel. At this time, the calcium content in the molten steel is controlled at 0.0020%-0.0030%.

[0017] Option 5 is the preferred option of the basic option. In S4, the amount of ferrotitanium added is calculated based on the amount of molten steel, the titanium content in ferrotitanium and the recovery rate to ensure that the titanium recovery rate is 82%.

[0018] Option six is the preferred option of the basic option. In S4, the composition of ferrotitanium includes titanium: 69-72w%, aluminum: 0.5-0.6w%, silicon: 0.35-0.40w%, carbon: 0.05-0.08w%, manganese: 0.38-0.60w%, phosphorus: ≤0.03w%, and sulfur: ≤0.015w%; it combines with the carbon in the steel to form stable titanium carbide (TiC), which acts as a nucleation particle to refine the grains, reduce the intergranular corrosion of the steel, and improve the corrosion resistance and welding performance of the material.

[0019] Option seven is the preferred option of the basic option. In S4, the flow rate of bottom-blown argon stirring is 10 to 20 NL / min, which is convenient for bottom-blown argon stirring desulfurization.

[0020] Option eight is the preferred option of the basic option. In S5, B2O3 is added to the protective slag used for casting in an amount of 0.55w%, and the content of B2O3 is 1.0-1.5w%; this is convenient for lowering the crystallization temperature of the protective slag.

[0021] Option nine is the preferred option of the basic option. In S6, the total reduction rate of rough rolling is 86-86.36%, the cumulative reduction rate of finishing rolling is 93.0-93.3%, and the thickness of the finished steel plate is 2.0-2.5 mm; the finished product rate of the rolled steel plate is ensured.

[0022] Scheme 10, which is the preferred basic scheme, in S6, the yield strength Rt of the steel plate after rolling 0.5 The tensile strength is 728~760MPa, and the tensile strength R m 912~952MPa, yield strength ratio Rt 0.5 / R m ≤0.81, elongation after fracture A 50mm The steel structure is ferrite + pearlite, the grain size is 11 to 11.5, the steel banded structure is not greater than 0.5, the non-metallic inclusion detection standard in steel is ASTM, and the D-type fine inclusions are 0.5 level. The performance of the finished steel plate is improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 This is a metallographic structure diagram of an ultra-high strength weathering steel regulated by phosphorus according to the present invention;

[0024] Figure 2 This is a non-metallic inclusion detection diagram of ultra-high strength weathering steel based on phosphorus regulation according to the present invention. DETAILED DESCRIPTION

[0025] The present invention will be further described in detail below through specific embodiments:

[0026] A preparation method of ultra-high strength weathering steel based on phosphorus regulation, wherein the composition weight percentage of the weathering steel includes C: 0.04-0.06w%, Si: 0.30-0.50w%, Mn: 0.45-0.55w%, Cu: 0.22-0.30w%, Cr: 1.25-1.35w%, P: 0.075-0.085w%, S≤0.005w%, Al: 0.025-0.040w%, Ti: 0.085-0.10w%, Ca: 0.0015-0.0035w%, N≤0.0050w%, and the rest is Fe and unavoidable impurities, and further comprises the following steps:

[0027] S1. First, pre-treat the molten iron to make the S content in the molten iron ≤ 0.003w%;

[0028] S2. Add the pretreated molten iron into a top-bottom combined-blowing converter for oxygen blowing smelting, control the converter endpoint C content to 0.03-0.045w%, P content ≤ 0.010w%, S content of the molten steel ≤ 0.0070w%, N content ≤ 0.0020w%, and the converter tapping temperature to 1630-1660°C;

[0029] S3, after the converter smelting is completed, steel is tapped. During the converter tapping process, pre-melted slag is first added to the ladle. The amount of pre-melted slag added is 300kg per furnace of steel. The main components of the pre-melted slag include: CaO content 35-40w%, Al2O3 content 36-40w%, CaF2 content ≤5w%, Al content 15-18w%. After the converter taps, the pre-melted slag melts rapidly, and the slag density is lower than that of the molten steel. Therefore, it floats on the surface of the molten steel, isolating the molten steel from the air. When the converter taps to 1 / 3 of the molten steel, low-carbon ferrochrome and low-carbon ferromanganese are added to the ladle. The carbon content of low-carbon ferrochrome is ≤0.3w%, the chromium content is 70w%, and the rest are unavoidable impurities. The carbon content of low-carbon ferromanganese is not more than 0.20w%, the manganese content is greater than 90w%, and the rest are unavoidable impurities. The addition amount of low-carbon ferrochrome is 18-18.5kg per ton of steel, and the addition amount of low-carbon ferromanganese is 3.5-4.0kg per ton of steel. When the converter taps to 2 / 3 of the molten steel volume, ferroaluminum is added to the molten steel. The addition amount of ferroaluminum is 1.0-1.2kg per ton of steel. The temperature of the molten steel in the ladle is controlled at 1575-1590℃.

[0030] S4. Before refining, the molten steel is first fed with aluminum wire for deoxidation, and then the ladle is sent to the LF furnace for refining. The initial refining temperature of the LF furnace is not lower than 1570℃, and the power-on temperature-raising time is not more than 20 minutes. Active lime and bauxite are added to each furnace of steel when the LF furnace is powered on. 2 to 3 minutes after the power is started, the foaming agent is added in three equal amounts. The time interval between each addition is 5 minutes. The foaming agent is a mixture of limestone and dolomite with a mass ratio of 3:2 and a particle size of 5 to 30 mm. The addition amount is 70 to 80 kg per furnace of steel. 90 to 110 kg of aluminum particles are added 10 minutes after the power is started. After the white slag is formed for 10 minutes, the bottom blowing argon is stirred for desulfurization for 5 minutes. The addition of ferrotitanium is calculated according to the amount of molten steel, the titanium content in ferrotitanium and the recovery rate to ensure that the titanium recovery rate is 82%. The addition amount of titanium is 0.085-0.10w%. The components of ferrotitanium include titanium: 69-72w%, aluminum: 0.5-0.6w%, silicon: 0.35-0.40w%, carbon: 0.05-0.08w%, manganese: 0.38-0.60w%, phosphorus: ≤0.03w%, sulfur: ≤0.015w%, and then bottom blowing argon and stirring for 12-16 minutes. The flow rate of bottom blowing argon and stirring is 10-20NL / min. After refining in the LF furnace, the molten steel is fed into 220-350m Calcium line, at this time, the calcium content in the molten steel is controlled at 0.0020% to 0.0030%, the recovery rate of elemental titanium is greater than 75%, the titanium content is controlled at 0.085 to 0.10w%, and other elements meet the control requirements for smelting finished molten steel. The molten steel is then continuously cast and the cooling time is greater than 4 to 6 minutes before pouring; the final slag composition of LF furnace refining is: CaO content 55 to 60w%, SiO2 content 10 to 15w%, FeO + MnO content ≤ 1.0w%, Al2O3 content 27 to 30w%, MgO content ≤ 5w%. By increasing the Al2O3 content, the viscosity of the slag is guaranteed, so that the LF slag achieves the best adsorption. Inclusion capacity: After LF refining, the S content of the molten steel is ≤0.005w%, the P content is 0.075-0.085w%, the nitrogen content of the molten steel is ≤0.0045w%, the molten steel temperature is 1590-1600℃, the total LF refining time is controlled within 55 minutes, and the nitrogen increase in the molten steel during the refining process is less than 0.0015%. The sulfur and nitrogen contents must be strictly controlled during the LF refining process. Due to the high activity of titanium and its strong ability to combine with oxygen, in order to effectively prevent the formation of titanium oxides and control the formation of large titanium carbonitride particles, the nitrogen content in the molten steel must be strictly controlled, and the aluminum content is accurately controlled at 0.025-0.040w%.

[0031] S5. During the continuous casting of slabs, low-viscosity continuous casting protection slag is used. The viscosity of the protection slag at 1300°C is 0.12-0.14 Pa·s. The binary basicity CaO / SiO2 of the protection slag is 1.2-1.3, which enhances the adsorption capacity of Al2O3 and forms a high CaO slag system to stably absorb TiO2 to form perovskite (CaTiO3). The CaF2 content in the protection slag is 4-5w%, avoiding the formation of high-melting-point TiN-TiO2 composite inclusions, which destroy the silicate network and titanium oxide chain, and the molten steel The superheat is 25-32°C, and the insertion depth of the submerged nozzle in the molten steel of the crystallizer is 150-160mm. This reduces continuous casting slag and reduces the risk of crusting on the high-titanium steel liquid surface. B2O3 is added to the mold flux used for casting at an addition amount of 0.55w%, and the B2O3 content is 1.0-1.5w%, which reduces the crystallization temperature of the mold flux. The continuous casting casting speed is controlled at 1.2-1.3m / min. The hot acid dip low-magnification test of the continuous casting slab shows that the center segregation of the slab is not greater than level 1.0 (Mannesmann standard).

[0032] S6. The slab after continuous casting is hot rolled to prevent hot rolling cracks. The charging temperature is 450-620℃, the slab heating temperature is 1240-1260℃, the rough rolling end temperature is 1140-1155℃, the total rough rolling reduction is 86-86.36%, the finishing rolling start temperature is 890-930℃, the finishing rolling end temperature is 875-895℃, the finishing rolling cumulative reduction is 93.0-93.3%, the thickness of the finished steel plate is 2.0-2.5mm, the steel plate after finishing rolling is laminar cooled, the laminar cooling cooling rate is 15-18℃ / s, the coiling temperature is 565-580℃, and the yield strength Rt of the steel plate after rolling is 2.0-2.5mm. 0.5 The tensile strength is 728~760MPa, and the tensile strength R m 912~952MPa, yield strength ratio Rt 0.5 / R m ≤0.81, elongation after fracture A 50mm It is 22.5-27%, the steel structure is ferrite + pearlite, the grain size is 11-11.5, the steel banded structure is not greater than 0.5 level, the non-metallic inclusion detection standard in steel is ASTM, and the D type fine inclusion is 0.5 level.

[0033] Table 1 - Comparison of composition and properties of weathering steel smelting products

[0034]

[0035]

[0036] The calcium content of the finished weathering steel in the above table is 0.0015~0.0035w%; among them, the thickness of the steel plates No. 1, 2, 3, 4, 5, and 6 is 2.0mm, the thickness of the steel plates No. 7 and 8 is 2.2mm, and the thickness of the steel plates No. 9 and 10 is 2.5mm.

[0037] The above is only an embodiment of the present invention, and the common knowledge such as the specific structure and characteristics of the scheme is not described in detail here. It should be pointed out that for those skilled in the art, without departing from the structure of the present invention, several variations and improvements can be made, which should also be regarded as the scope of protection of the present invention, and these will not affect the effect of the implementation of the present invention and the practicality of the patent. The scope of protection required by this application shall be based on the content of its claims, and the specific implementation methods and other records in the specification can be used to interpret the content of the claims.

Claims

1. A method for preparing ultra-high strength weathering steel based on phosphorus regulation, characterized in that: The composition mass percentage of weathering steel includes C: 0.04-0.06w%, Si: 0.30-0.50w%, Mn: 0.45-0.55w%, Cu: 0.22-0.30w%, Cr: 1.25-1.35w%, P: 0.075-0.085w%, S≤0.005w%, Al: 0.025-0.040w%, Ti: 0.085-0.10w%, Ca: 0.0015-0.0035w%, N≤0.0050w%, and the rest is Fe and unavoidable impurities, and further includes the following steps: S1. First, pre-treat the molten iron to make the S content in the molten iron ≤ 0.003w%; S2. Add the pretreated molten iron into a top-bottom combined-blowing converter for oxygen blowing smelting, control the converter endpoint C content to 0.03-0.045w%, P content ≤ 0.010w%, S content of the molten steel ≤ 0.0070w%, N content ≤ 0.0020w%, and the converter tapping temperature to 1630-1660°C; S3, after the converter smelting is completed, tapping is carried out. During the converter tapping process, pre-melted slag is first added to the ladle. The amount of pre-melted slag added is 300kg per furnace of steel. When the converter taps to 1 / 3 of the molten steel volume, low-carbon ferrochrome and low-carbon ferromanganese are added to the ladle. When the converter taps to 2 / 3 of the molten steel volume, ferroaluminum is added to the molten steel. The amount of ferroaluminum added is 1.0-1.2kg per ton of steel. The temperature of the molten steel in the ladle is controlled to be 1575-1590°C. S4. Before refining, the molten steel is first fed with aluminum wire for deoxidation, and then the ladle is sent to the LF furnace for refining. The initial refining temperature of the LF furnace is not lower than 1570℃, and the power-on temperature-raising time is not more than 20 minutes. Active lime and bauxite are added to each batch of steel when the LF furnace is powered on. Foaming agent is added in three equal amounts 2 to 3 minutes after the power is turned on, with an interval of 5 minutes between each addition. 90 to 110 kg of aluminum particles are added 10 minutes after the power is turned on. After 10 minutes of white slag formation, argon is blown from the bottom for desulfurization for 5 minutes, and then ferrotitanium is added. After bottom blowing and stirring for 12 to 16 minutes, the molten steel is continuously cast and the cooling time is more than 4 to 6 minutes before pouring. S5. During the continuous casting of slabs, a low-viscosity continuous casting mold slag is used. The viscosity of the mold slag at 1300°C is 0.12-0.14 Pa·s, the binary basicity CaO / SiO2 of the mold slag is 1.2-1.3, the CaF2 content in the mold slag is 4-5w%, the molten steel superheat is 25-32°C, the insertion depth of the submerged nozzle in the molten steel in the crystallizer is 150-160mm, the continuous casting casting speed is controlled at 1.2-1.3m / min, and the center segregation of the continuously cast slabs is not greater than level 1.0 according to the low-power detection of hot acid immersion of the continuously cast slabs; S6. The slab after continuous casting is hot rolled, the furnace charging temperature is 450-620°C, the slab heating temperature is 1240-1260°C, the end temperature of rough rolling is 1140-1155°C, the start temperature of finishing rolling is 890-930°C, the end temperature of finishing rolling is 875-895°C, the steel plate after finishing rolling is laminar cooled, the cooling rate of laminar cooling is 15-18°C / s, and the coiling temperature is 565-580°C.

2. The method for preparing ultra-high strength weathering steel based on phosphorus regulation according to claim 1, characterized in that: In S3, the main components of the pre-melted slag include: CaO content 35-40w%, Al2O3 content 36-40w%, CaF2 content ≤5w%, and Al content 15-18w%.

3. The method for preparing ultra-high strength weathering steel based on phosphorus regulation according to claim 1, characterized in that: In S4, the foaming agent is a mixture of limestone and dolomite with a mass ratio of 3:2, a particle size of 5 to 30 mm, and an addition amount of 70 to 80 kg per heat of steel.

4. The method for preparing ultra-high strength weathering steel based on phosphorus regulation according to claim 1, characterized in that: In S4, the molten steel after refining in the LF furnace is fed into the 220-350m calcium wire.

5. The method for preparing ultra-high strength weathering steel based on phosphorus regulation according to claim 1, characterized in that: In S4, the amount of ferrotitanium added is calculated according to the amount of molten steel, the titanium content in the ferrotitanium and the recovery rate, ensuring that the titanium recovery rate is 82%.

6. The method for preparing ultra-high strength weathering steel based on phosphorus regulation according to claim 1, characterized in that: In S4, the composition of ferrotitanium includes titanium: 69-72w%, aluminum: 0.5-0.6w%, silicon: 0.35-0.40w%, carbon: 0.05-0.08w%, manganese: 0.38-0.60w%, phosphorus: ≤0.03w%, and sulfur: ≤0.015w%.

7. The method for preparing ultra-high strength weathering steel based on phosphorus regulation according to claim 1, characterized in that: In S4, the flow rate of bottom-blown argon stirring is 10 to 20 NL / min.

8. The method for preparing ultra-high strength weathering steel based on phosphorus regulation according to claim 1, characterized in that: In S5, B2O3 is added to the protective slag used for casting, the added amount is 0.55w%, and the content of B2O3 is 1.0-1.5w%.

9. The method for preparing ultra-high strength weathering steel based on phosphorus regulation according to claim 1, characterized in that: In S6, the total reduction ratio of rough rolling is 86 to 86.36%, the cumulative reduction ratio of finish rolling is 93.0 to 93.3%, and the thickness of the finished steel plate is 2.0 to 2.5 mm.

10. The method for preparing ultra-high strength weathering steel based on phosphorus regulation according to claim 1, characterized in that: In S6, the yield strength Rt of the steel plate after rolling 0.5 The tensile strength is 728~760MPa, and the tensile strength R m 912~952MPa, yield strength ratio Rt 0.5 / R m ≤0.81, elongation after fracture A 50mm It is 22.5-27%, the steel structure is ferrite + pearlite, the grain size is 11-11.5, the steel banded structure is not greater than 0.5 level, the non-metallic inclusion detection standard in steel is ASTM, and the D type fine inclusion is 0.5 level.